(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
In this work, various loads of nanomaterials and aliphatic dendritic polymerswere mixed with fibre grade PET (Polyethylene terephthalate) to study its dye ability, thermal and thermal-mechanical properties. A twin screw extruder equipped with sheet (profile) die was used for mixing the compounds. Thermal behaviour of the neat PET and the compounded sheet samples were studied using differential scanning calorimeter and dynamic mechanical thermal analysis. It was observed that the T_g of samples decreased gradually by increasing the load of Boltorn H40 as a nanomaterial additive while the T_m remained almost the same. The difference between the glass transition temperature for neat PET and the compounded sample including 3% additive was about seven degrees. In spite of the decline in T_g, the moduli of samples containing additive increased as revealed by DMTA analysis. The presence of this dendritic polymer in compounded PET acted as a cross linking or antiplastisizing agent and made the fibre grade PET compounds more compact than pure PET. So the disperse dye molecules neither were able to stay between the molecules of compounded PET nor were able to trap between the dendritic branches.